Analisis Pengaruh Usia,Pelatihan,dan Pengalaman Kerja Terhadap Produktivitas Tenaga Kerja Industri Pangan Di Kecamatan Ampenan Kota Mataram - Kiyasatina, Baiq Diyan; Wahidin, Wahidin; Handayani, Tuti (Jurnal Ilmu Ekonomi, 2024)
Research with the title Analysis of the Influence of Age, Training and Work Experience on the Productivity of Food Industry Workers in Ampenan District, Mataram City with the aim of analyzing how much influence these variables have on the productivity of Food Industry Workers in Mataram City and what efforts are made by the industry in increase labor productivity. The results of the research can be concluded that: The variables of age, training and work experience simultaneously influence the productivity of food industry workers in Ampenan sub-district. The age variable partially has a positive and significant effect on the productivity of food industry workers in Ampenan sub-district. The training variable partially has a positive and significant effect on significantly to the productivity of food industry workers in Ampenan sub-district. Work experience variables partially have a positive and significant effect on the productivity of food industry workers in Ampenan sub-district. Keywords: Productivity,Age, Training, Work Experience